PENGARUH PENDAPATAN ASLI DAERAH (PAD), DANA ALOKASI UMUM (DAU), DANA ALOKASI KHUSUS (DAK) DAN DANA BAGI HASIL (DBH) TERHADAP INDEKS PEMBANGUNAN MANUSIA (IPM) DENGAN BELANJA MODAL SEBAGAI VARIABEL INTERVENING (STUDI PADA KABUPATEN DAN KOTA DI KEPULAUAN RIAU TAHUN 2019-2024) - SitI Rabiyah; Fatahurrazak Fatahurrazak; Hadli Lidya Rikayana (CV. Denasya Smart Publisher, 2026)
This study analyzes the influence of Regional Original Revenue (PAD), General Allocation Fund (DAU), Special Allocation Fund (DAK), and Revenue Sharing Fund (DBH) on the Human Development Index (HDI) with Capital Expenditure as an intervening variable in 7 regencies/cities in the Riau Islands Province for the 2019–2024 period. Using a quantitative method and path analysis on 42 observations, the results show that PAD, DAU, and DAK have a significant effect on HDI, while DBH and Capital Expenditure do not. Capital Expenditure also does not act as a mediator. These findings indicate that the allocation of capital expenditure has not been optimal in supporting short-term HDI improvement, thus requiring more targeted planning in basic service sectors.